Jacob Mincer Prize (Journal of Labor Economics, 2017)
Previous articleNext article FreeJacob Mincer PrizePDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreThe 2017 Jacob Mincer Prize is awarded to Francine Blau, the Frances Perkins Professor of Industrial and Labor Relations and Professor of Economics at Cornell University and a fellow and past president of the Society of Labor Economists (SOLE).Fran’s first publication in 1972, while she was still a graduate student at Harvard, was titled “Women’s Place in the Labor Market,” and it foreshadowed major themes of her research career and of labor economics more generally. Fran identified persistent occupational segregation of males and females as a major obstacle to women’s progress and showed that there had been little change in the degree of segregation despite rapid growth in female labor force participation after World War II. In addition, the ratio of female to male wages seemed stuck at three-fifths, a ratio that Victor Fuchs had traced back to biblical times. Fran identified important feedback effects on both the supply and demand sides that were responsible for a persistent equilibrium that relegated women to low-wage female jobs. On the demand side, firms were reluctant to make firm-specific investments in women who they believed would likely leave their jobs to have babies or follow their husbands. Reinforcing this, she argued that girls were socialized to take course work that would prepare them for female-dominated occupations with transferable skills, like teaching, nursing, or office work.As Fran was preparing to enter the male-dominated field of economics, she predicted that a movement of women into male occupations would reduce gender wage differentials as would movement of men into previously female occupations. In a 1994 paper—one of many in a career-long collaboration with her husband, Larry Kahn—they noted that American women had been “swimming upstream” in an economy that was growing increasingly unfavorable to low-wage workers. On average, women were in relatively low-wage occupations and had less labor market experience at a time that wage inequality was rising and returns to labor market experience were high.The fact that the actual wage gap was narrowing was both remarkable and puzzling when looking only at traditional human capital measures. Fran and Larry’s explanation for female success in the labor market focused on changes in the wage structure that were shifting against male-dominated occupations in manufacturing in favor of occupations with skill mixes associated with female occupations. Their linking of inequality of the wage structure and changes in the occupational distribution in the case of women anticipated the vast subsequent literature on the polarization of the occupations and growth of inequality in wages and incomes that has affected the entire labor force in the United States and many other countries.In a comprehensive and authoritative survey of the field they pioneered that is forthcoming in the Journal of Economic Literature, Fran and Larry include 20 of their own papers and books, along with a vast and fruitful body of literature that is continuing to develop new theories, data, and estimation methods to further our understanding of women’s role in the economy. This work includes international comparisons, family economics, migration, personnel economics, industrial organization, asymmetric information, expectations about future payoffs to current curricular choices, social and cognitive psychology, and much more. The forces affecting the work, wages, and well-being of women and men that Fran identified in her first paper while still a graduate student have continued to play themselves out in much the way that she identified early on.Fran’s lifetime contributions to labor economics and to women’s equality have been recognized in many ways. In addition to being a fellow and past president of SOLE, she has served as president of the Midwest Economic Association and vice president of the American Economic Association (AEA), and she has served on numerous editorial boards. Fran was the first woman to win the IZA Prize for outstanding accomplishment in labor economics. She was chair of the AEA’s Committee on the Status of Women and recipient of its Carolyn Shaw Bell Award. It is most fitting and wholly deserved for Fran Blau to receive the Jacob Mincer Award “In recognition of a lifetime of contributions to the field of labor economics” for the line of work that Mincer himself introduced into modern labor economics.2017 Jacob Mincer Award Nominating Committee:Katherine AbrahamHenry S. Farber (ex officio)Claudia GoldinChunhui JuhnThomas LemieuxChristopher R. TaberRobert J. Willis (chair) Previous articleNext article DetailsFiguresReferencesCited by Journal of Labor Economics Volume 35, Number 3July 2017 Published for the Society of Labor Economists, Economics Research Center/ NORC Article DOIhttps://doi.org/10.1086/692687 © 2017 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.